Study of excitonic superfluidity in Cu2O. - Benson, Éric. (University of Ottawa (Canada), 1995)
Excitonic transport measurements in ultra-pure semiconducting Cu$\sb2$O crystals were performed over a wide range of exciton densities at liquid Helium temperatures. The excitons were created with a high power pulsed Nd:YAG laser in the Cu$\sb2$O over a 3 mm$\sp2$ area and in a thin layer a few micrometers thick. The excitons then migrated over several millimeters through the crystal and were measured at the opposite sample face in time resolve using the exciton mediated photovoltaic effect. At low exciton density the transport is diffusive as expected and the results are well fitted by a diffusion equation. However at high exciton densities the transport becomes ballistic and a reduction in the size of the exciton distribution becomes apparent. Furthermore, the density at which there is a crossover from diffusive to ballistic behaviour follows a $T\sp{3/2}$ temperature dependence and is of the same order of magnitude as the predicted critical density for Bose-Einstein condensation. Pump-probe experiments with two laser pulses separated by a variable time delay allowed the formation of two exciton packets separated by the distance traveled by the first packet during the time delay. The experiments confirmed the attractive nature of a Bose condensate with other condensates and normal Bose particles, and revealed the formation of a soliton condensate. We conclude that the results presented in this work are consistent with the condensation and superfluid transport of excitons in Cu$\sb2$O.
Keywords: Physics, Condensed Matter.